The Orphan Human Pregnane X Receptor Mediates the Transcriptional Activation of CYP3A4 by Rifampicin through a Distal Enhancer Module - Goodwin, Bryan; Hodgson, Ecushla; Liddle, Christopher (Molecular pharmacology, 1999)
Cytochrome P-450 3A4 (CYP3A4), the predominant cytochrome P-450 expressed in adult human liver, is subject to transcriptional induction by a variety of structurally unrelated xenobiotics, including the antibiotic rifampicin. The molecular mechanisms underlying this phenomenon are poorly understood. We transfected a human liver-derived cell line (HepG2) with various CYP3A4-luciferase reporter gene constructs containing a nested set of 5′-deletions of the CYP3A4 5′-flanking region. Rifampicin-inducible transcription of the reporter gene was observed only with the longest construct, which encompassed bases –13000 to +53 of CYP3A4 (3-fold induction). The responsive region was functional regardless of its position or orientation relative to the proximal promoter of CYP3A4 and was capable of conferring rifampicin-inducible expression on a heterologous promoter. Further deletion mutants localized the induction to bases –7836 to –7607. In vitro DNase I footprint analysis of this region revealed four protected sites (FP1, FP2, FP3, and FP4). Two of these sites, FP3 (bases –7738 to –7715) and FP4 (bases –7698 to –7682), overlapped binding motifs for the orphan human pregnane X receptor (hPXR). Cotransfection of responsive constructs with a hPXR expression vector substantially increased the rifampicin-inducibility to ∼50-fold. In addition, the rifampicin-responsive constructs were strongly activated by a range of CYP3A inducers. Finally, we demonstrate cooperativity between elements within the distal enhancer region and cis-acting elements in the proximal promoter of CYP3A4. Our results provide evidence for the existence of a potent enhancer module, 8 kb distal to the transcription start point, which mediates the transcriptional induction of CYP3A4 by activators of hPXR.